2019
DOI: 10.1080/14763141.2019.1620321
|View full text |Cite
|
Sign up to set email alerts
|

Static stretching time required to reduce iliacus muscle stiffness

Abstract: Static stretching (SS) is an effective intervention to reduce muscle stiffness and is also performed for the iliopsoas muscle. The iliopsoas muscle consists of the iliacus and psoas major muscles, among which the former has a greater physiological crosssectional area and hip flexion moment arm. Static stretching time required to reduce muscle stiffness can differ among muscles, and the required time for the iliacus muscle remains unclear. The purpose of this study was to investigate the time required to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Nakamura et al (2013) reported that both passive torque of the ankle joint and myotendinous junction displacement of the gastrocnemius changed after 2 min of static stretching and further lowered or increased after 5 min. Nojiri et al (2019) also found that the stiffness of the iliacus muscle declined at 1 min and at further 5 min of static stretching. The carry-over effect of stretching repetitions in the current study was more early found compared with those reported in previous studies.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Nakamura et al (2013) reported that both passive torque of the ankle joint and myotendinous junction displacement of the gastrocnemius changed after 2 min of static stretching and further lowered or increased after 5 min. Nojiri et al (2019) also found that the stiffness of the iliacus muscle declined at 1 min and at further 5 min of static stretching. The carry-over effect of stretching repetitions in the current study was more early found compared with those reported in previous studies.…”
Section: Discussionmentioning
confidence: 73%
“…Of interest is that the stretching duration that immediately changes the muscle stiffness may differ in the target muscle. The stretching durations for 3 min, 2 min, 1 min, and 20 s were needed to change the muscle stiffness of the hamstrings (Nakamura et al, 2019), the gastrocnemius (Nakamura et al, 2013), the iliacus (Nojiri et al, 2019), and infraspinatus (Kusano et al, 2017), respectively. One of the factors that determine the stretching duration could be the muscle volume, more precisely, the cross-sectional area of the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in MTU stiffness partially contributes to lower the muscles’ capacity to generate torque (Matsuo et al, 2013). Recently, Nojiri et al (2019) demonstrated that the stiffness of the iliacus muscle decreased after 60 s of StS and further decreased after 5 min of StS in healthy male participants aged 23 years. Also, Konrad et al (2019) examined the time course of the changes in MTU mechanical properties of the gastrocnemius medialis after 5 min of StS in healthy male and female participants aged 25 years.…”
Section: Methodsmentioning
confidence: 99%
“…The time required to decrease the shear modulus and muscle‐tendon stiffness is different for each muscle. The decrease in shear modulus of the infraspinatus and iliopsoas requires 20 22 and 60 67 s, respectively, and the muscle‐tendon unit stiffness of the hamstrings and triceps surae requires 180 60,68,69 and 90 70 s, respectively. The difference between the muscles of long‐term static stretching training needs to be examined.…”
Section: Discussionmentioning
confidence: 99%